Pengembangan Modul Pembelajaran IPS Berbasis Kearifan Lokal (Maccerang Manurung) untuk Memperkuat Identitas Budaya dan Keterampilan Sosial - Sinta prahastin; Nurfadila Sjjarif; Firdaus W Suhaeb (STKIP Subang, 2026)
Social Studies (IPS) learning plays an important role in strengthening students’ cultural identity and social skills amid the rapid flow of globalization, which may erode local cultural values. This study aims to develop a Social Studies learning module based on the local wisdom of maccerang manurung as a contextual and relevant learning resource. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects involved teachers and secondary school students, while data were collected through observation, interviews, questionnaires, and documentation. The results showed that the developed module was considered feasible based on material expert validation, media expert validation, and user responses, and was effective in improving students’ understanding of local cultural values and social skills such as cooperation, communication, and empathy. Therefore, the Social Studies learning module based on the local wisdom of maccerang manurung can serve as an innovative teaching material to strengthen students’ cultural identity and social skills.